IDENTIFIKASI INTERAKSI MANUSIA DAN KOMPUTER BERBASIS COMPUTER VISION SYNDROME PADA UNIT REFINERY CENTRAL CONTROL ROOM - Muchamad Sugarindra; Zuhdi Allamsyah (Teknoin, 2017)
Technology usage for elevating work productivity still cannot be separated from human control. Therefore, company performance will be affected by the operator’s quality. Computer interaction, as an example of technology used, is dominating the work performed. Continuous and repetitive used will affect the occupational health. Hence, it will increase the risk of Computer Vision Syndrome (CVS). Computer Vision Syndrome (CVS) is defined as a collection of symptoms related to eyes caused by computer usage and affected by several factors. Those factors can be divided into individual and external factors. The problem of this research is to determine whether there is a relationship between CVS with the internal and external factors. The type of research is non experimental quantitative with correlational research design and cross sectional approach. While the respondents are twelve operators of Refinery Central Control Room (RCCR). Spearman Rho test is used to find relationship among variables. The results from this research indicate that there is correlation between age and the resulting CVS symptoms with the value of p is 0,04 (p<0 05). But, there are no correlation between CVS and other factors (eye glasses, length of work duration, break time, eye sides distance). Not all internal and external factors have correlation with the accuracy of CVS. This Research shows correlation between internal factors and CVS. It was aging. Aging is degenerative processes which lower the body function periodically. Therefore, there are correlation between age and CVS. But, there are not for other factors.